2021
DOI: 10.18393/ejss.942488
|View full text |Cite
|
Sign up to set email alerts
|

Effects of deforestation on soil properties and organic carbon stock of a hillslope position land in Black Sea Region of Turkey

Abstract: Article InfoThe effects of deforestation on soil properties and soil organic C (SOC) stock in adjacent pasture and forest areas located on the same hillslope position were investigated. The soil properties measured in the forest site had higher coefficient of variation compared with pasture site. Deforestation made almost 50 years ago significantly increased bulk density (Db), soil pH, exch. Mg and significantly decreased total porosity (F), gravimetric moisture content (W), EC, exch. K, soil organic matter (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…The loss of soil SOM may be related soil water erosion and mineralization (Sabir et al, 2004;Gülser et al, 2021). These results are similar to those found by several authors.…”
Section: Effects Of Deforestation On Soil Chemical Propertiessupporting
confidence: 86%
See 2 more Smart Citations
“…The loss of soil SOM may be related soil water erosion and mineralization (Sabir et al, 2004;Gülser et al, 2021). These results are similar to those found by several authors.…”
Section: Effects Of Deforestation On Soil Chemical Propertiessupporting
confidence: 86%
“…These changes in the physical properties of the soil observed in cultivated soils compared to forest soils are the result of deforestation and subsequent tillage, which favors the erosion of the finest soil particles. Several studies have shown dramatic changes in particle size distribution after deforestation followed by cultivation (Nunes et al, 2012;Assefa et al, 2020;Gülser et al, 2021). The hydrodynamic behavior of the soil depends on several physical characteristics such as porosity and bulk density which appear to be most strongly and rapidly affected by forest clearing followed by cultivation (Table.1).…”
Section: Effects Of Deforestation On Soil Physical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation